THE EFFECTIVENESS OF CERTAIN PHYSICAL ABILITIES AND THEIR RELATIONSHIP TO THE DEVELOPMENT OF GOALKEEPERS' SKILL PERFORMANCE IN THE IRAQI PROFESSIONAL FOOTBALL LEAGUE - Assistant lecturer. Mohammed Mnaathar; Dr. Safaa Kadhim Radhi Al-Ghazali (Proximus Journal Publishing, 2025)
The study aimed to identify the relationship between specific physical abilities and certain offensive skills of goalkeepers in the Iraqi Professional Football League. The researchers hypothesized a statistically significant relationship between these physical abilities and offensive skills among the study sample.
Keywords: offensive; identify; specific